Etude des caractéristiques physico-chimiques des poudres de lait utilisées au niveau de la filiale GIPLAIT cas de la «laiterie du littoral de Mostaganem ». - KESSAS, Rania (My University, 2020)
The comparative study of the physico-chemical characteristics of the milk powder susedat the level of the subsidiary GIPLAIT " The Coastal Diary of Mostaganem " provide us the opport unity to recognise the physico-chemical quality of the milk powder susedat the level of the production of this dairyin dustry unit. The two raw materials, AGROPUR 0% and AGROPUR milk powders 26%, have good solubility-dispersibility-wettability indices and an appreciable physico-chemical quality from the Dornic acidity, pH, humidity, fat and proteinmatter contents point of view. Preliminary results show compliance for a good reconstitution of liquid milk; increasing its market value and suitability for dairy process in gwith good technological performance. For the elaboration of the specifications defining the criteria for choosing and allocating milk powder to processing, other specifications are to bestudied in the future including microbiological and sensory criteria
Keywords: Milk powders; Physico-chemical quality; Aptitude for processing